Sustainable Entrepreneurship: The Potential of Campus Waste in Making Entrepreneurial Products with High Selling Value - Rizka Novembrianto; Mohamad Mirwan; Dea Febrica Ervina; Mar'atus Sholikhah; Pandu Wicaksono (Future Science, 2023)
UPN